Correction to: Cohort profile: the Saskatchewan Rural Health Study—adult component - Punam Pahwa; Masud Rana; William Pickett; Chandima P. Karunanayake; Khalid Amin; Niels Koehncke; Valerie Elliot; Louise Hagel; Josh Lawson; Donna Rennie; Shelley Kirychuk; Bonnie Janzen; et al. (BMC Research Notes, 2018)
Abstract Following publication of the original article [1] the authors notified Production that the names of three authors—Valerie Elliot, Louise Hagel, and Roland Dyck—had been unintentionally omitted in the final online version of the manuscript. The corrected author list is shown in this Correction.